Recovering bird diversity by landscaping a landfill: early stages of succession - Solonen, Tapio (Ornis Svecica, 2007)
A Finnish pilot project of landscaping a landfill is aimed at creating conditions for a diversified and abundant flora and fauna. In 1997—2005, one part, a recent sand heaping mound was managed, while a second part, a former communal waste dump, was left for free vegetation succession. The birds of the open landfill area (45 ha) and surrounding forest (30 ha) were censused by territory mapping during four breeding seasons (1997, 2003—2005). The changes in the avifauna of the landscaped part were compared to those of the unmanaged one and the surrounding forest. In the open habitats, the total abundance of ground-nesting birds remained relatively stable while the species nesting in scrub clearly increased. However, the ground-nesters increased in the recently landscaped heaping mound, but decreased in the unmanaged area. The bird diversity seemed to change in the expected manner, following the rapid early succession of vegetation. Accordingly, continuous management is needed to keep the species of the most open habitats as permanent members of the local avifauna.